Dynamic spectrum allocation strategy with probabilistic feedback mechanism and performance analysis - Shun-fu JIN; Shi-ying GE; Zhan-qiang HUO (Tongxin xuebao)
By introducing probabilistic feedback mechanism and energy detection threshold to cognitive radio networks,a novel dynamic spectrum allocation strategy is proposed to trade off the throughput and average delay of secondary users,as well as meet various network requirements.Considering the imperfect sensing results of secondary users,a kind of priority queueing model is established,in which two classes of users may interfere with each other,then the state transition probability matrix is constructed.Employing the method of matrix-geometric solution,the stationary distribution of system model is derived.Accordingly,the expressions for the performance measures in terms of channel utilization,throughput of secondary users,average delay of secondary users and interference ratio of primary users are given.With numerical experiments and system simulations,the effectiveness of the proposed dynamic spectrum allocation strategy is verified.Finally,the optimal design of energy detection threshold is provided.